Application of Urban Sustainable Design Strategies for Development and Rehabilitation of Al-Qahad Heritage Village. Issue 1 (3rd December 2018) - Aldossary, Naief A.
This paper investigates and analyses the redesigning of a heritage village in the southern region of Saudi Arabia to determine the impact of sustainable design strategies and green open spaces for the village rehabilitation. Heritage village development is an important step to consider for sustainable urban planning and design due to its influence in urban development, the local economy, and historical conservation. Al-Qahad heritage village has been selected as the case study due to its involvement with different historical domestic buildings, military castles, and mosques and its location on the main highway between Albaha and other regions. Furthermore, this heritage village reflects in its urban identity the local environment, social culture, and local construction materials and vernacular architecture. The applied approach involved visiting Al-Qahad heritage village for (a) analysis of the site and environmental conditions, (b) mobility survey analysis, and (c) the application of urban sustainable design strategies for redesigning Al-Qahad heritage village. The site visit included a physical survey to determine the current condition of buildings regarding heights, conditions, land use, and construction materials used. The output of the study is to redesign the heritage village including suggesting some other urban facilities, such as a museum, hotel, and other social activities to attract visitors and rehabilitate the village. The study highlights the importance of many urban sustainable design strategies that can be applied in other heritage villages in Saudi Arabia to protect and conserve the historical buildings and invest in these facilities for tourism purposes. Saudi Arabia is a nation rich with heritage villages, which are found across the country especially in the southern region. The study concludes by offering several recommendations for developers and investors.